Пошаговое объяснение:
Для удобства вычислений сгруппируем по парам дроби, дающие в сумме 1, а оставшиеся сложим, приведя к общему знаменателю (5*6*7=210)
1/2+1/3+1/4+1/5+1/6+1/7+2/3+2/4+2/6+2/7+3/4+3/5+3/6+3/7+4/5+4/7+5/6+6/7=
1/2+ (1/3+2/3) + (1/4+3/4) + (1/5+4/5) + (1/6+5/6) + (1/7+6/7) +2/4+ (2/6+3/6) +2/7+3/5+ (3/7+4/7) = 1/2 + 1 + 1 + 1 + 1 + 1 + 2/4+ 5/6 + 2/7+3/5 + 1 = 6 + (1/2 + 2/4) + (5/6 + 2/7+3/5) = 6 + 1 + (5*35/21 0 + 2*30/210 + 3*42/210) = 7 + (175+60+126)/210 = 7 + 361/210 = 7 + 1 151/210 = 8 151/210
-15х+10=-4х+131
-15х+4х=131-10
-11х=121
х=121/(-11)
х= - 11